Molecular epidemiological studies of Campylobacter isolated from different sources in New Zealand between 2005 and 2015 : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Manawatu, New Zealand - Nohra, Antoine (Massey University, 2017)
Campylobacteriosis is one of the most important food-borne diseases worldwide, and a significant health burden in New Zealand. C. jejuni is the predominant species worldwide, accounting for approximately 90% of human cases, followed by C. coli. The first study evaluated whether the time elapsing from sampling to culture has an impact on the recovery rate of Campylobacter, and explored whether some sequence types are more likely than others to be missed due to delayed culture. The study revealed that, whereas delayed culture may affect the recovery rate of Campylobacter, there was no evidence of a bias due to specific sequence types being under detected. The second study aimed to analyse the differences in the Campylobacter viable counts and in population genetic structure between chicken drumsticks and whole carcass meat for retail sale. The results indicate that the Campylobacter population genetic structure did not differ between the two types of retail chicken meat. However, the difference in Campylobacter viable counts suggest that consumption of different chicken meat products may pose different risks of campylobacteriosis associated with an exposure to different infection doses. In the third study, we genotyped C. coli isolates collected from different sources between 2005 and 2014, to study their population structure and estimate the contribution of each source to the burden of human C. coli disease. Modelling indicated ruminants and poultry as the main sources of C. coli infection. The fourth study aimed to genotype C. jejuni isolates collected between 2005 and 2015 from different sources, to assess changes in the molecular epidemiology of C. jejuni following the food safety interventions implemented by the New Zealand poultry industry in 2007/2008. Modelling indicated that chicken meat from ‘Supplier A’ was the main source of C. jejuni human infection before the interventions; but after the interventions, ruminants became the main source of infection, followed by chicken meat from Supplier A. This thesis has made us aware of the aetiology of C. coli infections and the change in the attribution of C. jejuni infections. These findings should be used in developing further strategies to reduce the total burden of human campylobacteriosis.
Keywords: Campylobacter infections; Epidemiology; Molecular epidemiology; New Zealand; Research Subject Categories::MEDICINE::Social medicine::Public health medicine research areas